Fitness effects of one-year soccer training of 8-10 and 10-12-year-old school children - Michailidis, Y.; Metaxas, T.; Stefanidis, P.; Christoulas, K. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of the study was to investigate the effect of one-year soccer training on physical fitness performance, of under ten (U10) and under twelve (U12) youth levels. METHODS: The study included 28, 10-year-old children, and 28, 12-year-old children. In the U12 group, 19 children participated only in the physical fitness sessions at school (control group) and 9 children in four extra soccer trainings (soccer group). In the U10 group, 11 children participated only in the physical fitness sessions at school (control group) and 17 children in four extra soccer trainings (soccer group). Height, body weight, body fat, standing long jump, 30 m sprint, sit and reach test, abdominal test and Yo-Yo IE1 tests were performed at the beginning and at the end of the season. RESULTS: School physical education programs and soccer training cannot affect anthropometric characteristics like body fat and Body Mass Index. Soccer groups improve their performances at all fitness tests (P<0.05). The U10 control group did not increase its performance in abdominal test and the U12 level control group did not improve in the abdominal test nor Yo-Yo IE1 Test. Soccer groups in all ages indicated greater improvements than control groups (P<0.05). CONCLUSIONS: In conclusion soccer training four times per week can improve the physical fitness of U10 and U12 children.